Characterization of morphological changes within stromata during sexual reproduction in Aspergillus flavus. (2nd September 2020) - Luis, Jane Marian; Carbone, Ignazio; Payne, Gary A.; Bhatnagar, Deepak; Cary, Jeffrey W.; Moore, Geromy G.; Lebar, Matthew D.; Wei, Qijian; Mack, Brian; Ojiambo, Peter S.
ABSTRACT: Aspergillus flavus contaminates agricultural products worldwide with carcinogenic aflatoxins that pose a serious health risk to humans and animals. The fungus survives adverse environmental conditions through production of sclerotia. When fertilized by a compatible conidium of an opposite mating type, a sclerotium transforms into a stroma within which ascocarps, asci, and ascospores are formed. However, the transition from a sclerotium to a stroma during sexual reproduction in A. flavus is not well understood. Early events during the interaction between sexually compatible strains of A. flavus were visualized using conidia of a green fluorescent protein (GFP)-labeled MAT1-1 strain and sclerotia of an mCherry-labeled MAT1-2 strain. Both conidia and sclerotia of transformed strains germinated to produce hyphae within 24 h of incubation. Hyphal growth of these two strains produced what appeared to be a network of interlocking hyphal strands that were observed at the base of the mCherry-labeled sclerotia (i.e., region in contact with agar surface) after 72 h of incubation. At 5 wk following incubation, intracellular green-fluorescent hyphal strands were observed within the stromatal matrix of the mCherry-labeled strain. Scanning electron microscopy of stromata from a high- and low-fertility cross and unmated sclerotia was used to visualize the formation and development of sexual structures within the stromatal and sclerotial matrices, starting at the time of crossing and thereafter every 2 wk until 8 wk of incubation. Morphological differences between sclerotia and stromata became apparent at 4 wk of incubation. Internal hyphae and croziers were detected inside multiple ascocarps that developed within the stromatal matrix of the high-fertility cross but were not detected in the matrix of the low-fertility cross or the unmated sclerotia. At 6 to 8 wk of incubation, hyphal tips produced numerous asci, each containing one to eight ascospores that emerged out of an ascus following the breakdown of the ascus wall. These observations broaden our knowledge of early events during sexual reproduction and suggest that hyphae from the conidium-producing strain may be involved in the early stages of sexual reproduction in A. flavus . When combined with omics data, these findings could be useful in further exploration of the molecular and biochemical mechanisms underlying sexual reproduction in A. flavus .